315 A patient survey to identify atopic dermatitis prescription treatment access barriers. (25th January 2023) - Loiselle, Allison R; Thibau, Isabelle J C; Guadalupe, Michele; Butler, Lisa; Begolka, Wendy Smith
Abstract: Atopic dermatitis (AD) is the most prevalent form of eczema and is a chronic disease with a relapsing-remitting nature. Multiple treatment options exist, yet little is known about patients' ability to obtain recommended prescription treatments. The aim of this web-based survey was to ascertain the frequency, causes and patient impact of insurance delays and denials for AD prescription treatments. Adult AD patients (18 + years) or caregivers of pediatric AD patients were recruited to complete a survey about experiences with prescription treatment access in the last 12 months. Responses from 1234 AD patients (42.0 ± 16.7 years) and 248 caregivers (8.5 ± 4.7 years) were included in the analysis; 55.4% ( n = 680) reported moderate or severe AD. Overall, there were 789 insurance delays or denials for AD prescriptions, with 37.0% (457/1234) of respondents experiencing at least one in the past 12 months. Overall, the majority of delays/denials were for topical steroids (38.3%; 302/789), which is likely due to the high number of patients using one or more topical steroid prescriptions (82.5%; 1018/1234). However, the highest individual drug class burden was on biologics, for which 38.7% of all prescriptions (122/315) faced a delay or denial. Coverage denials were caused primarily by step therapy (25.5%), and delays by prior authorization (61.1%), and only 62.0% of respondents said they would know what to do if they faced an issue getting a prescription covered by their insurer. Patient-reported impacts of prescription denials and delays included: AD flares (85.0%; n = 255), needing alternate medications (72.3%; n = 217), emergency care (49.0%; n = 147) and giving up on treatment altogether (59.0%; n = 177). Patients with AD and their families frequently experience issues obtaining recommended therapies which can result in detrimental health and quality of life impacts. As many as one-third of patients may not know how to respond if their prescriptions are met with insurance delays or denials, further exacerbating those impacts. These data may help identify strategies to improve timely and beneficial therapeutic access.